Modeling the Impact of Biopores on Root Growth and Root Water Uptake. Issue 1 (28th March 2019) - Landl, Magdalena; Schnepf, Andrea; Uteau, Daniel; Peth, Stephan; Athmann, Miriam; Kautz, Timo; Perkons, Ute; Vereecken, Harry; Vanderborght, Jan
Abstract : Core Ideas: A 3D soil–root model was used to investigate root–biopore interactions. Known effects of biopores on root growth, i.e., increased root length and depth were reproduced. Despite reducing root–soil contact, biopores led to increased water uptake in dry periods. Biopores had a larger impact on water uptake for more compact and less conductive soils. Roots are known to use biopores as preferential growth pathways to overcome hard soil layers and access subsoil water resources. This study evaluates root–biopore interactions at the root‐system scale under different soil physical and environmental conditions using a mechanistic simulation model and extensive experimental field data. In a field experiment, spring wheat ( Triticum aestivum L.) was grown on silt loam with a large biopore density. X‐ray computed tomography scans of soil columns from the field site were used to provide a realistic biopore network as input for the three‐dimensional numerical R‐SWMS model, which was then applied to simulate root architecture as well as water flow in the root–biopore–soil continuum. The model was calibrated against observed root length densities in both the bulk soil and biopores by optimizing root growth model input parameters. By implementing known interactions between root growth and soil penetration resistance into our model, we could simulate root systems whose response to biopores in the soil corresponded well to experimental observations described in the literature, such as increased total root length and increased rooting depth. For all considered soil physical (soil texture and bulk density) and environmental conditions (years of varying dryness), we found biopores to substantially mitigate transpiration deficits in times of drought by allowing roots to take up water from wetter and deeper soil layers. This was even the case when assuming reduced root water uptake in biopores due to limited root–soil contact. The beneficial impact of biopores on root water uptake was larger for more compact and less conductive soils.